Analyzing Illegal Trade On The Dark Web - Zaid Mundher (International Journal Of Electrical Engineering and Inteligent Computing, 2025)
Internet can be divided, in terms of accessibility, into three main categories: Surface web, Deep web, and Dark web. The dark part is considered the most dangerous of these types due to the difficulty of tracking its users and the anonymity it offers, making it widely used for illegal activities. This research aims to measure the prevalence of illegal activities in Iraq and some neighboring countries, specifically Syria, Saudi Arabia, and Iran. The activities tracked include: drug trafficking, fake documents, and weapons trafficking. The search engine "Ahmia" was used to collect dark web links (with the .onion extension) as an initial stage. In the second stage, the Tor network was used to access these links to obtain more information from each page. A dataset of approximately 5,000 pages was created and analyzed to generate a set of insights related to the data. The results showed that Iraq appears more prominently compared to neighboring countries, reflecting the widespread use of dark web sites, as will be discussed later in this work.